Geochemical Tracer in Coral as a Sea Surface Temperature Proxy: Records from Jukung Coral - S. Y. Cahyarini; J. Zinke (Journal of Engineering and Technological Sciences, 2010)
Sr/Ca  has been analyzed from coral core from the Seribu Islands  reef complex  i.e  Jukung  Island.  SST  from  ERSST  dataset  and  air  temperature measured at Jakarta is used for Sr/Ca calibration. The results show that Jukung Island  coral  Sr/Ca  correlates  better  with  SST  than  with  air  temperature.  A comparison  between  the  Sr/Ca  records  with  the  Nino  3.4  index  shows  that Jukung  coral  sites  indicate  warming  sea  surface  temperatures  during  the beginning  of El Nino  events followed by cooling temperatures at the end of El Nino years.